Resume Parsing and Standardization - Shivratri, Pooja; Kshirsagar, Preeti; Mishra, Rashmi; Damania, Ronit; Prabhu, Nandana (International Journal of Computer Sciences and Engineering, 2015)
Internet plays a crucial role in our daily life, from shopping to banking one can do anything just by a single click. Similarly, seeking jobs through online portals has become much convenient for the candidates as well as the recruiters. These portals help recruiter to find the perfect candidate and the candidate to get their perfect job. Automated and user-friendly software is being created which endows with a solution to parse all the resumes and provides a quality candidates required for the job. This paper deals with the parsing application developed for the resumes received in multiple formats like doc, docx, pdf, txt. When a company has a vacant position, it receives thousands of resumes for a single position. The concerned authorities have to go through each parameter of the resume and then select the candidates, for the interview. However, this system transforms original resumes into a standard format which contains only desired details of the candidate.